Розробка компонентів інформаційної системи книжкового дискусійного онлайн клубу-магазину - Шраменко, К. І. (ХНУРЕ, 2024)
This report was created to cover the topic of developing components of an information system for an online book discussion club. This system is designed to sell exclusive books signed by the authors, as well as to provide notifications and bookings for irregular meetings with such authors to discuss their work. Any user of the system can buy a book signed by the author of his or her favorite book, as well as make an appointment with the author or with like-minded people to discuss the meaning, theme or theories of a particular book. The system is designed as a web-based system with a three-tier architecture. The layers of such a system are mssql as the data layer, asp.net as the system logic layer, and angular as the client side of the application.
Keywords: система обговорень; база даних книг; управління замовленнями